2023
DOI: 10.7717/peerj.15589
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin-affected endothelial dysfunction and altered gut microbiota in mice with heart failure

Abstract: Aim To investigate the potential microbiome profile of a mouse model with heart failure (HF) during dapagliflozin treatment. Method An HF model was constructed in 8-week-old male mice, and cardiac tissues were analyzed using histological staining. Hemodynamic indexes were measured, and fecal samples were collected for 16S rDNA sequencing. Chao1, Shannon, and Simpson were used for α-diversity analysis. b-Diversity analysis was conducted using principal coordinate analysis (PCoA) and non-metric multidimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These clinical beneficial effects of dapagliflozin rely on several pathophysiologica mechanisms that have been investigated in different experimental and clinical studies Thus, experimental studies have shown in different animal models with HF that dapagli flozin inhibits ventricular remodeling, attenuates cardiometabolic dysregulation and dia betes-induced diastolic dysfunction, reduces cardiac fibrosis and inflammation, improve These clinical beneficial effects of dapagliflozin rely on several pathophysiological mechanisms that have been investigated in different experimental and clinical studies. Thus, experimental studies have shown in different animal models with HF that dapagliflozin inhibits ventricular remodeling, attenuates cardiometabolic dysregulation and diabetesinduced diastolic dysfunction, reduces cardiac fibrosis and inflammation, improves aorta sympathetic tone and endothelial dysfunction [109][110][111][112][113][114][115][116][117][118]. The impact of dapagliflozin on cardiac remodeling has been confirmed in patients with chronic HF in the DAPA-MODA study, with significant improvements in left atrial volume, left ventricular geometry parameters and natriuretic peptides levels, after only 6 months of treatment [119].…”
Section: Discussionmentioning
confidence: 86%
“…These clinical beneficial effects of dapagliflozin rely on several pathophysiologica mechanisms that have been investigated in different experimental and clinical studies Thus, experimental studies have shown in different animal models with HF that dapagli flozin inhibits ventricular remodeling, attenuates cardiometabolic dysregulation and dia betes-induced diastolic dysfunction, reduces cardiac fibrosis and inflammation, improve These clinical beneficial effects of dapagliflozin rely on several pathophysiological mechanisms that have been investigated in different experimental and clinical studies. Thus, experimental studies have shown in different animal models with HF that dapagliflozin inhibits ventricular remodeling, attenuates cardiometabolic dysregulation and diabetesinduced diastolic dysfunction, reduces cardiac fibrosis and inflammation, improves aorta sympathetic tone and endothelial dysfunction [109][110][111][112][113][114][115][116][117][118]. The impact of dapagliflozin on cardiac remodeling has been confirmed in patients with chronic HF in the DAPA-MODA study, with significant improvements in left atrial volume, left ventricular geometry parameters and natriuretic peptides levels, after only 6 months of treatment [119].…”
Section: Discussionmentioning
confidence: 86%
“…Paraprevotella has been identified as a noteworthy bacterium implicated in cardiac structural and functional impairment in a rat model of heart failure. Desulfovibrio, as a detrimental genus, has a role as a pivotal sulfate-reducing bacterium in the gut microbiota, introducing hydrogen sulfide and lipopolysaccharide into compromised tissues [177]. Another antidiabetic drug that appears to be able to modulate the microbiome is acarbose, an intestinal alpha-glucosidase inhibitor.…”
Section: The Role Of Gm Modulation In the Gut-kidney-heart Axismentioning
confidence: 99%
“…Obesity is a metabolic disease correlated to an increased risk of multiple extradigestive complications. Nutritional intervention, a crucial management tool, can positively affect weight management, associated disease risk control, and the occurrence of extradigestive complications in patients with obesity by modifying the dietary structure and providing appropriate nutrients[ 1 - 5 ]. The global prevalence of obesity is increasing and is closely related to the development of extradigestive complications, such as cardiovascular disease (CVD), type 2 diabetes mellitus, and non-alcoholic fatty liver disease (NAFLD).…”
Section: Introductionmentioning
confidence: 99%